Pengaruh Kecerdasan Intelektual, Kecerdasan Spiritual, Kecerdasan Emosional Dan Love Of Money Terhadap Perilaku Etis Calon Sarjana Akuntansi Di Universitas Buana Perjuangan Karawang - Fitri Handayani; Fista Apriani Sujaya; Awaliawati Rachpriliani (Journal of Economic, Bussines and Accounting (COSTING), 2023)
In creating professionals who have special competencies in accordance with the field of science and study, students must still be equipped with high ethics in order to achieve these goals. However, inversely proportional to the expected ethical behavior expectations, there are many acts of academic fraud that occur and little by little begin to fade ethical values in accounting students where they will become professionals in the future.The purpose of this research is to get the empirical evidence of intellectual intelligence, spiritual intelligence, emotional intelligence, and love of money against ethical behavior of accounting graduate candidates at Buana Perjuangan University, Karawang. The research approach in this study is a categorical approach using primary data. The sampling technique is nonprobability sampling with a purposive-sampling method. The number of samples in this study is 110 samples. The analysis technique is multiple linear regression. The results of this study show that intellectual intelligence, spiritual intelligence, emotional intelligence, and love of money has a positive effect on the ethical behavior of an accounting graduate candidate. The practical implications for accounting graduate candidate are that they must prepare for their ethical behavior before entering the working environment. Keywords: academic fraud, professionals, ethical behavior of undergraduate candidates accounting